The physiologic and therapeutic role of Heparin in implantation and placentation - Quaranta, Michela; Erez, Offer; Mastrolia, Salvatore Andrea; Koifman, Arie; Leron, Elad; Eshkoli, Tamar; Mazor, Moshe; Holcberg, Gershon (PeerJ PrePrints, 2014)
Implantation, trophoblast development and placentation are crucial processes in the establishment and development of normal pregnancy. Abnormalities of these processes can lead to pregnancy complications named the great obstetrical syndromes (preeclampsia, intrauterine growth restriction, fetal demise, premature prelabor rupture or membranes, preterm labor, and recurrent pregnancy loss). There is mounting evidence regarding the physiological and therapeutic role of heparins in the establishment of normal gestation and as a modality for treatment and prevention of pregnancy complications. In this review we will summarize the properties and the physiological contribute of heparins to the success of implantation and placentation and normal pregnancy.
Keywords: glycosaminoglycan; Glycosaminoglycan; Trophoblast; Selectins; Cadherins; HB-EGF; Matrix metalloproteinases; Immune system